Partnership: Basis for future policies - Peter Michael Rügner (Intereconomics, 1975)
Changes that have taken place in world trade and politics during the first half of the seventies do not remain without impact on the guidelines of development policies. It is highly likely that future development policies will have to be based increasingly on partnership and not so much, as in the past, on aid pure and simple.
Keywords: 330; Development Strategy